Online Gaming Addiction and Self-Reported Emotional Responses Among Married Men in Sidoarjo, Indonesia: A Cross-Sectional Study - Mundakir Mundakir; Muhammad Luqman Fariz; Fathiya Lutfil Yumni; Reliani Reliani (Indonesian Academia Health Sciences Journal, 2026)
Background: Problematic online gaming may interfere with emotional control and family functioning, but evidence among married adult men in Indonesian community settings remains limited. Objective: To examine the association between online gaming addiction severity and self-reported emotional response levels among married male heads of household in Sidoarjo, Indonesia. Methods: This analytical cross-sectional study included 91 married male heads of household aged 28-43 years who played online games and were recruited by purposive sampling from two neighborhood units in Gelam Village, Sidoarjo, during July-August 2023. Gaming addiction was assessed using the 21-item Game Addiction Scale, and emotional responses were assessed with a 15-item study-specific questionnaire covering anger, sadness, fear, and happiness. Descriptive statistics and Spearman rank correlation were used. Results: Severe gaming addiction was reported by 46 participants (50.5%), and a high emotional response level was reported by 41 participants (45.1%). Among participants with severe gaming addiction, 26 of 46 (56.5%) had a high emotional response level, compared with 1 of 14 (7.1%) among those with mild gaming addiction. Gaming addiction severity was positively associated with emotional response level (Spearman rho = 0.371, p < .001). Conclusion: Greater online gaming addiction severity was associated with higher self-reported emotional response levels among married men in this community sample. Because the design was cross-sectional and both measures were self-reported, the findings do not establish causality. Community and mental health nursing programs should consider family-centered screening, emotion-regulation support, and referral for individuals with persistent gaming-related impairment.